Enhanced Recovery After Surgery (ERAS): A Perspective Review of Postoperative Pain Management Under ERAS Pathways and Its Role on Opioid Crisis in the United States. Issue 3 (March 2020) - Echeverria-Villalobos, Marco; Stoicea, Nicoleta; Todeschini, Alexandre B.; Fiorda-Diaz, Juan; Uribe, Alberto A.; Weaver, Tristan; Bergese, Sergio D.
Abstract : Objectives: The objective of this study was to review the current scientific evidence on the role of Enhanced Recovery After Surgery (ERAS) implementations in reducing postoperative opioid consumption and their potential association with the risk reduction for long-term opioid use, physical opioid dependency, and opioid addiction. Methods: A literature search was conducted using the following medical subject heading keywords: "postoperative pain, " "postoperative pain management, " "multimodal analgesia, " "ERAS, " "Enhanced Recovery, " "opioid-free analgesia, " or "opioid crisis." Discussion: Identification and management of pre-existing psychosocial factors, comorbid pain entities, and chronic opioid use have a significant impact on the severity of postoperative pain. Different multimodal analgesia approaches have been associated with reduced postoperative pain scores and opioid consumption. Health care providers, patients, and family members should recognize the advantages of opioid-free analgesia techniques in postoperative pain management. As part of ERAS protocols, transitional pain services may consider current therapeutic alternatives for acute and long-term pain management that include minimizing perioperative opioid use and establishing adequate opioid prescription practices.